PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM KERJA SEKOLAH TERHADAP KINERJA GURU - Sutianingsih, Sutianingsih (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
The existence of the phenomenon of teacher performance degradation,can be seen fromteachers who do not do their job properly, the teachers whoteach only highly educated butless attention function. Improved performance canbe achieved by improving teachers' leadership style of principals and schoolwork climate. Therefore, the central issue in thisstudy is how much influence theprincipal's leadership style and school climate work onteacher performance.Thisstudy aims to analyze the influence of principal leadership style on teacherperformance and school climate effects work on teacher performance. Thehypothesis is that there is a positive effect between: the principal's leadershipstyle on teacher performance and the climate of the school work on teacherperformance.This study belongs to the kind of quantitative research using the surveymethod and descriptive analytic approach. The samples used were from allpopulation of 50 teachers SMA/SMKBina Nusantara Semarang. Techniquesof data collection through questionnaires. Data analysis technique used is thePearson product moment correlation, determination, and multiple linearregression. Furthermore, the data that has been collected is processed and theninterpreted, analyzed, and described according to the problem andresearchobjectives.Based on the results of this study concluded that theprincipal's leadership style and school climate is partially working (people) onthe performance of teachers.